Glaucoma Syndromes: Insights into Glaucoma Genetics and Pathogenesis from Monogenic Syndromic Disorders - Balikov, Daniel A.; Jacobson, Adam; Prasov, Lev (Genes, 2021)
Monogenic syndromic disorders frequently feature ocular manifestations, one of which is glaucoma. In many cases, glaucoma in children may go undetected, especially in those that have other severe systemic conditions that affect other parts of the eye and the body. Similarly, glaucoma may be the first presenting sign of a systemic syndrome. Awareness of syndromes associated with glaucoma is thus critical both for medical geneticists and ophthalmologists. In this review, we highlight six categories of disorders that feature glaucoma and other ocular or systemic manifestations: anterior segment dysgenesis syndromes, aniridia, metabolic disorders, collagen/vascular disorders, immunogenetic disorders, and nanophthalmos. The genetics, ocular and systemic features, and current and future treatment strategies are discussed. Findings from rare diseases also uncover important genes and pathways that may be involved in more common forms of glaucoma, and potential novel therapeutic strategies to target these pathways.